2020
DOI: 10.3390/biomedicines8090309
|View full text |Cite
|
Sign up to set email alerts
|

Looking Inside the World of Granulosa Cells: The Noxious Effects of Cigarette Smoke

Abstract: The detrimental implications of tobacco smoke on systemic health have been widely established during the past few decades. Nonetheless, increasing evidence has begun to shed more light on the serious impact that smoke exposure could also have on mammal reproductive health in terms of overall ovarian dysfunction and gestation. A variety of these complications seem to be causally related to specific chemical substances contained in cigarette smoke and their possible effects on ovarian tissues and cells, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“… 30 Secondly, the positive correlation between smoking and androgen metabolism was reported. 31 For example, some chemical substances contained in cigarette smoke could cause changes in luteal steroidogenesis, affecting progesterone and estradiol production, as well as suppression of the oocyte-cumulus complex expansion. 32 Another influence of smoking could be its effect on insulin.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Secondly, the positive correlation between smoking and androgen metabolism was reported. 31 For example, some chemical substances contained in cigarette smoke could cause changes in luteal steroidogenesis, affecting progesterone and estradiol production, as well as suppression of the oocyte-cumulus complex expansion. 32 Another influence of smoking could be its effect on insulin.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to tobacco smoke constituents is known to potentially harm human reproductive health, with particular reference to the ovary. Several experimental studies conducted in vitro or in vivo showed that nicotine (with its principal metabolite-cotinine), together with benzo[a]pirene (BaP), dimethylbenz[a]anthracene (DMBA) and cadmium, exert central roles in the process of ovotoxicity, influencing the steroidogenesis, the correct follicle development and the correct meiotic progression of the oocytes [ 2 , 4 , 5 ]. Although a number of studies have explored the mechanisms behind cigarette smoke-induced ovarian toxicity, the understanding of this process remains, so far, not completely elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 4000 chemicals that constitute cigarette smoke (CS), the polycyclic aromatic hydrocarbons (PAHs), nitrosamines, heavy metals, alkaloids and aromatic amines represent the most studied classes of toxicants [ 2 ]. The male and female reproductive systems represent sensitive targets of the harmful effects of cigarette smoke [ 3 , 4 , 5 ]. In women, cigarette smoke exposure is associated with earlier menopause and delayed conception [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations